Elasticity in Daily Life: A Potential Topics in Learning Physics - Andita, Naya; Rahmadani, Mutiara Rindi; Pratama, Tia Ayu Nafi; Mubarak, Husni; Fitriana, Fitriana; Lestari, Nurita Apridiana; Salsabila, Liya (International Journal of Research and Community Empowerment, 2024)
As a branch of natural science, physics explores the fundamental properties of matter and energy and their interactions. This study specifically examines the concept of elasticity—the ability of an object to return to its original shape after removing an external force—and equilibrium, which are crucial in understanding various physical phenomena. The research aims to highlight the practical applications of elasticity and equilibrium principles in daily life across multiple fields. Additionally, it seeks to underscore the importance of physics education in preventing misconceptions about these fundamental concepts. The findings suggest that effectively applying elasticity and equilibrium principles can enhance problem-solving in everyday scenarios. However, there is a critical need to improve physics education, particularly in literature and practical simulations, to mitigate common misconceptions and enhance understanding.